Ética no serviço social, ensino e aprendizagem : análise do curso Ética em Movimento na Bahia (2000-2017) - Nascimento, Adriana Antonia Alves do (2020)
The study on screen proposes the analysis of the teaching of ethics in Social Work defining as an object of study the development of the Ethics in Movement Course, in Bahia, from 2000 to 2017. Its main objective was to analyze the political, pedagogical proposal and methodological aspects of the referred course, implanted in the regional area following the deliberation of the Federal Council together with the Regional Social Service Councils in a national meeting of the category in 1999, given the need to deepen questions about ethics in the professional political sphere, in particular, the legal-operational guidelines, reflected in the treatment of ethical complaints within the scope of regional units. The research, therefore, analyzed the development of the Ethics in Movement Course in Bahia from 2000 to 2017, taking into account the syllabus, the methodology adopted for the presentation of the themes, teaching material used, course load, profile of / the facilitators, places where classes are held and evaluations made by course participants about the training activity. Methodologically this research is of a descriptive nature, with a qualitative basis and adopted as technical procedures the documentary and bibliographic research with a qualitative approach, guided by the perspective of materialism-historical-dialectic, which guides the analysis of the object of study beyond its appearance, and makes it possible to apprehend its essence, its structure and its historical and social dynamics. The empirical field was the Regional Council of Social Service of Bahia (CRESS / Ba) and the main source of research was the pedagogical proposals of the courses, schedules, reports and evaluations of the course participants. During the period studied, 23 groups from the Ethics in Movement course in Bahia were held with a political pedagogical proposal for the courses guided by a concept of socially referenced ethics, based on critical social theory and whose central ethical value is freedom. The adopted methodology encourages reflective thinking, an inventive attitude and the establishment of commitments to individual and collective transformations, in connection with the professional project of Social Work. In the understanding of course participants, the most significant contribution was the possibility of reflecting ethically on professional practice, which implies self-criticism and reassessment of the practice, qualifying and improving the performance of social workers. We conclude that the implementation of the Ethics in Movement course in Bahia has contributed to qualify professional practice by stimulating critical thinking as the ethics debate equips subjects to face the challenges posed to professional practice.